2020
DOI: 10.1186/s12875-020-01228-4
|View full text |Cite
|
Sign up to set email alerts
|

Factors that facilitate recognition and management of domestic violence by primary care physicians in a Chinese context - a mixed methods study in Hong Kong

Abstract: Background Domestic violence is common in the community. Many of its victims present to primary care physicians (PCPs) but are not being recognized and managed. The barriers, with specific reference to a Chinese cultural context, were investigated earlier. This paper explored the factors which facilitated the process of recognizing and managing suspected cases of domestic violence by PCPs in Hong Kong. Methods Four focus group interviews were conducted to explore in-dep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
1
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 27 publications
2
1
0
4
Order By: Relevance
“…This study’s results are similar to the results reported by a study conducted in Japan, according to which recognizing women as victims of violence is usually easier when it involves physical signs and interventions are essentially based on the curative model ( 15 ) . In addition, the authors note that for workers to deal with these situations, communication and continuity of care are essential so that these situations can be identified and prevented at the beginning, avoiding it from getting worse.…”
Section: Discussionsupporting
confidence: 88%
“…This study’s results are similar to the results reported by a study conducted in Japan, according to which recognizing women as victims of violence is usually easier when it involves physical signs and interventions are essentially based on the curative model ( 15 ) . In addition, the authors note that for workers to deal with these situations, communication and continuity of care are essential so that these situations can be identified and prevented at the beginning, avoiding it from getting worse.…”
Section: Discussionsupporting
confidence: 88%
“…Hegarty, Spangaro, et al (2020), also reported that healthcare providers wanted clear processes for screening women for domestic violence. Similar findings were concluded in a mixed method study with primary healthcare physicians in Hong Kong (Lam et al, 2020); and a questionnaire of Royal College of Physicians and Surgeons in Canada (Long et al, 2019). The perinatal period is an opportune time to screen for domestic violence due to this being a high contact period for women with their primary‐based healthcare providers (Campo, 2015), therefore, more focus on supporting healthcare providers with tangible screening tools and protocols is recommended.…”
Section: Discussionsupporting
confidence: 79%
“…Village health volunteers use non-fixed criteria to assess household abuse risk, making it difficult to determine if domestic violence will be prioritized on the community agenda. Effective communication and interpretation are essential for the network's perception mechanism (Lam et al, 2020).…”
Section: Role and Methods For Dealing With Domestic Violencementioning
confidence: 99%